Babesia Life Cycle – When Phylogeny Meets Biology. Issue 5 (May 2019) - Jalovecka, Marie; Sojka, Daniel; Ascencio, Mariano; Schnittger, Leonhard
Abstract : Although Babesia represents an important worldwide veterinary threat and an emerging risk to humans, this parasite has been poorly studied as compared to Plasmodium, its malaria-causing relative. In fact, Babesia employs highly specific survival strategies during its intraerythrocytic development and its intricate journey through the tick vector. This review introduces a substantially extended molecular phylogeny of the order Piroplasmida, challenging previous taxonomic classifications. The intriguing developmental proficiencies of Babesia are highlighted and compared with those of other haemoparasitic Apicomplexa. Molecular mechanisms associated with distinctive events in the Babesia life cycle are emphasized as potential targets for the development of Babesia -specific treatments. Highlights: Evolutionary diversification of vertebrate hosts is the major driving force of Piroplasmida phylogeny. Remarkable diversity of the genus Babesia represents one of the greatest challenges for the development of generic antibabesial therapeutics. Specific events of the Babesia life cycle represent mandatory adaptations of Babesia to the tick vector. Analogies between Plasmodium and intra-tick development of Babesia opens avenues for developing novel intervention strategies.